Safety and Microbiological Quality - Montet, Didier (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The safety and microbiological quality of fermented foods covers complementary aspects of such products. Food fermentation is primary intended to improve food preservation, thereby modifying food properties. However, the management of chemical and microbiological hazards is a leading aspect for innovative processing in this domain. Similarly, microbiological quality in fermented foods is of peculiar importance: all microorganisms with a positive effect, including probiotic bacteria, fermentative bacteria, Saccharomyces and non-Saccharomyces yeasts, can be relevant. The fitness of pro-technological microorganisms impacts nutritional quality, but also sensory properties and processing reliability. This book provides a broad view of factors which determine the safety and microbiological quality of fermented foods. A focus is made on the interconnection between starter properties and the expectations related to a probiotic effect. All chapters underline the involvement of fermented foods towards better resource management and increasing food and nutritional security, especially in developing countries.